The roads we follow - Deese, Nicole (Deese, Nicole. Fog Harbor romance, 2024)
"Aspiring writer Raegan Farrow learns about a tell-all on her famous mother's life that could tear their family apart but keeps it a secret as they embark on a cross-country road trip. While trying to uncover who's behind it, she learns their handsome driver has his own connection to her mother's past, and all their lives will be changed by journey's end"--